Game Technique and its Classification in the Process of Teaching Students to Volleyball - Elmonovich, Rozikov Normurod (Excellencia: International Multi-disciplinary Journal of Education (2994-9521), 2024)
The article discusses the work aimed at the development of volleyball sport, methods of selecting volleyball players in groups using regulatory tests and exercises, the acquisition of skills and abilities in the main forms of techniques and tactics of playing volleyball, as well as ways of their preparation.